The Myriad of Clinical Presentations of COVID-19: a Short Review - Nepal, Richa (Nepalese Medical Journal, 2020)
The ongoing pandemic of Coronavirus disease- 2019 is yet to be defeated. It is primarily a viral respiratory illness, with a myriad of clinical presentations being reported, since it was first identified towards the end of 2019 in China. Apart from the classical symptoms of fever, cough, and dyspnea, atypical presentations in COVID-19 patients, have puzzled healthcare workers worldwide. Patients with isolated non- respiratory complaints like diarrhea, vomiting, abdominal pain, skin rash, and confusion, have tested positive for severe acute respiratory syndrome coronavirus-2. The symptoms of olfactory and gustatory dysfunction have recently been added to the list for screening suspected cases after their prevalence was found to be high among COVID-19 patients. This article elaborates on the system-wise manifestations of COVID-19 and discusses the clinical implications of these aberrant presentations to healthcare workers.